Sociological Analysis on Effect of Self-Control on Youth Deviant Leisure (Case Study: The Youth of Babolsar City) - aliasghar firouzjaeian; Zahra Saadati (توسعه اجتماعی, 2021)
The importance of leisure is not overlooked by anyone in today's world full of tension, where people often feel tired because of their busy work. On the other hand, there is deviant leisure which can have many consequences as an activity that violates the ethical, moral and legal norms of the community. It endangers social security in society. This study examines the effect of self-control dimensions on the deviant leisure of youth. The general theory of crime admits that low self-control providing the context of deviant behavior. In this study, survey method was used and questionnaire was used to collect information. The population of this analysis includes all 18-35 years old youths in Babolsar. 400 youth with Cochran formula were selected by using multistage cluster sampling. We used face validity and Cronbach's alpha as reliability. Deviant leisure explained in tow types of obvious deviant leisure and latent deviant leisure. Latent deviant leisure was more than obvious deviant leisure. The results of Pearson correlation indicate that there is a significant relationship between low self-control and with deviant leisure. According to the research theoretical model test, which was carried out using structural equation modeling, it was found a positive effect of low self-control on deviant leisure (Beta=0/65). Also, the research components altogether could explain %43 of the variations of dependent variable (deviant leisure).in all it can says that persons that have low self-control, more do deviant leisure action in leisure times.